Promising practices for de-escalation and use-of-force training in the police setting: a narrative review. Issue 3 (13th November 2020) - Bennell, Craig; Blaskovits, Brittany; Jenkins, Bryce; Semple, Tori; Khanizadeh, Ariane-Jade; Brown, Andrew Steven; Jones, Natalie Jennifer
Abstract : Purpose: A narrative review of existing research literature was conducted to identify practices that are likely to improve the quality of de-escalation and use-of-force training for police officers. Design/methodology/approach: Previous reviews of de-escalation and use-of-force training literature were examined to identify promising training practices, and more targeted literature searches of various databases were undertaken to learn more about the potential impact of each practice on a trainee's ability to learn, retain, and transfer their training. Semi-structured interviews with five subject matter experts were also conducted to assess the degree to which they believed the identified practices were relevant to de-escalation and use-of-force training, and would enhance the quality of such training. Findings: Twenty practices emerged from the literature search. Each was deemed relevant and useful by the subject matter experts. These could be mapped on to four elements of training: (1) commitment to training (e.g. securing organizational support for training), (2) development of training (e.g. aligning training formats with learning objectives), (3) implementation of training (e.g. providing effective corrective feedback) and (4) evaluation and ongoing assessment of training (e.g. using multifaceted evaluation tools to monitor and modify training as necessary). Originality/value: This review of training practices that may be relevant to de-escalation and use-of-force training is the broadest one conducted to date. The review should prompt more organized attempts to quantify the effectiveness of the training practices (e.g. through meta-analyses), and encourage more focused testing in a police training environment to determine their impact.